Baicalin Protects Against Hypertension-Associated Intestinal Barrier Impairment in Part Through Enhanced Microbial Production of Short-Chain Fatty Acids - Wu, Dandan; Ding, Liliqiang; Tang, Xiaoting; Wang, Wenjian; Chen, Yu; Zhang, Teng (Frontiers in Pharmacology, 2019)
Impaired intestinal barrier plays an important role in the pathogenesis of hypertension primarily through promoting the development of chronic low-grade inflammation. Baicalin is the major flavonoid component of Scutellaria baicalensis Georgi, a medicinal plant commonly used for the treatment of inflammatory intestinal disorders and hypertension in traditional Chinese medicine. However, it remains to be elucidated whether baicalin alleviates hypertension-associated intestinal barrier impairment. The current study thus investigated the effects of baicalin on the intestinal barrier integrity, the intestinal expression of genes encoding proinflammatory factors and tight junction proteins, the serum levels of the inflammatory markers, the amount of fecal short-chain fatty acids (SCFAs) and the abundance of SCFAs-producing bacteria in the spontaneously hypertensive rats (SHRs). The results showed that baicalin alleviated the pathological lesions in the ilium and the proximal colon in the SHRs. Baicalin treatment resulted in decreased ileal and colonic expression of proinflammatory genes in the SHRs. In addition, baicalin treatment attenuated hypertension-associated intestinal hyperpermeability and decreased the serum levels of inflammatory indicators such as high-sensitivity C-reactive protein (hs-CRP), interleukin 1 beta, and IL-6 in the SHRs. The protective effect of baicalin on the intestinal integrity was also supported by well-preserved intestinal ultrastructure and increased intestinal expression of genes encoding tight junction proteins such as zonula occludens-1 (ZO-1), cingulin, and occludin in the SHRs. Lastly, baicalin treatment increased the amount of fecal SCFAs and the abundance of SCFAs-producing bacteria in the SHRs. In conclusion, the work here provides for the first time the morphological, biochemical, and molecular evidence supporting the protective effects of baicalin on the intestinal integrity in the SHRs, which may help better understand the therapeutic effects of S. baicalensis Georgi in the treatment of hypertension.